Pneumatosis Intestinalis and Intestinal Perforation in a Patient Receiving Tocilizumab - Ben JACOBS,; Ali JAWAD,; Zozik FATTAH, (Archives of Rheumatology, 2018)
In this article, we report a case of pneumatosis intestinalis associated with tocilizumab use. This is a unique case and may explain the increased rate of idiopathic bowel perforation among patients taking tocilizumab.